2007
DOI: 10.1269/jrr.06093
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose Radiation Increased the Therapeutic Efficacy of Cyclophosphamide on S180 Sarcoma Bearing Mice

Abstract: We examined whether low dose radiation (LDR) exposure (75 mGy) could increase the therapeutic efficacy of cyclophosphamide (CTX) by comparing the effects of tumor suppression, tumor cell apoptosis, cell cycle and proliferation of bone marrow in vivo. Kunming mice implanted with S(180) sarcoma cells were given 75 mGy whole body gamma-ray radiation exposure and CTX (300 mg/kg) by intraperitoneal injection 36 hours after LDR. Proliferation of bone marrow and tumor cells was analyzed by flow cytometry. Cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Subsequent research on this topic became a hotspot. Studies have found that normal cells including immune cells, blood cells [4–6], and spermatogonial cells [7] induced by LDR could cause an adaptive response. Thus, LDR improved organism immunity and enhanced the tolerance of normal tissue under radiation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research on this topic became a hotspot. Studies have found that normal cells including immune cells, blood cells [4–6], and spermatogonial cells [7] induced by LDR could cause an adaptive response. Thus, LDR improved organism immunity and enhanced the tolerance of normal tissue under radiation.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been extensively documented by many investigators with different experimental models, including cultured cells and experimental animals [811]. Experimental studies have proven that low doses of ionizing radiation induce various cancer types with various effects, including radioadaptive response, activation of immune functions, and enhancement of resistance to high-dose radiation at the initial slope of the cell survival curve [4, 12]. In recent years, studies on the effects of LDR have attracted the attention of scientists in radiation research [12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial membrane permeability and the alteration of membrane potentials are essential aspects in the apoptotic process, resulting in release of CytoC and initiation of apoptosis by activating the caspase reaction cascade. Yu et al (32) also discovered that LDR exposure (0.0075 Gy) increased the therapeutic efficacy of cyclophosphamide (CTX) to S180 sarcoma cells. The apoptosis of tumor cells increased significantly following LDR.…”
Section: Discussionmentioning
confidence: 99%
“…5 days after implantation of S180 sarcoma cells, the mice's tumor growth was observed every other day by measuring the maximum horizontal diameter (a) and the maximum vertical diameter (b) twice with slide gauge and then the average values were calculated. The tumor's volume (V) was calculated with the formula: V=1/2ab 2 (Yu et al, 2007). Then the tumor's growth graph was drawn.…”
Section: Tumor Growth Observation and Biopsy Examinationmentioning
confidence: 99%